UJI EFEK ANALGETIK ANTIPIRETIK EKSTRAK ETANOL ALFALFA (Medicago sativa) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Hesti Wulan; Uning Rininingsih EM.; Ika Puspitaningrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Analgesic is a group of drugs to relieve pain without erasing consciousness and antipyretic is a compound that can reduce fever. This study aims to verify the effects of analgesic and antipyretic and determine the effective dose of alfalfa ethanol extract (Medicago sativa) as an analgesic-antipyretic. Twenty-five male Wistar rats were divided into five groups. Group I (negative control), rats were treated with CMC-Na 0.5%. Group II (positive control), rats were treated with paracetamol 50 mg/kg BW. Rats in group III, IV, and V were treated with a suspension of the alfalfa ethanol extract (50; 100 and 200) mg/kg BW. Pain stimuli conducted by dipping a rat's tail into 40 °C hot water for 10 seconds. Response time to a painful stimulus were measured before and 30 minutes after treatment. Fever in rats induced with 0.2 mL DPT vaccine intramuscularly. Rectal temperature was measured before treatment (initial temperature), 60 minutes after the vaccine, and 30 minutes after treatment. Data response time to the stimulus of pain and rectal temperature were statistically Analyzed with a one-way ANOVA and Scheffe test at 95% confidence level. The results showed that the alfalfa ethanol extract can improve the response time to pain stimulation and decrease the rectal temperature of fever-induced rats with a DPT vaccine. The effective dose of alfalfa ethanol extract as an analgesic-antipyretic is 200 mg/kg BW. Key words: Alfalfa ethanol extract, analgesics, antipyretics